2016
DOI: 10.16920/jeet/2016/v0i0/85433
|View full text |Cite
|
Sign up to set email alerts
|

Activity Based Teaching Learning: An Experience

Abstract: The paper presents activity based teaching learning for undergraduate students. This also gives the analysis of the effectiveness of these activities. The objective of proposed pedagogical practice is to enhance the course learning, beyond the traditional mode. In the traditional mode of teaching the course was not able to make a positive impact on learning. This is because of monotonous lecturing and absence of activities.Activity Based Teaching Learning (ABTL) is an effort to overcome the limitations of trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…The research methodology was involved student surveys (end-semester and after-examination) with the validation with the results published by the Institution. The academic performance is considered sa the evaluation tool for the selected course (Patil et al 2016). Two surveys were taken at the end-semester opinions on the learning methodologies and the second one, after-examination surveys on how was the performance in the examination.…”
Section: E Case Study On Active Learning Methodologies In Engineerinmentioning
confidence: 99%
“…The research methodology was involved student surveys (end-semester and after-examination) with the validation with the results published by the Institution. The academic performance is considered sa the evaluation tool for the selected course (Patil et al 2016). Two surveys were taken at the end-semester opinions on the learning methodologies and the second one, after-examination surveys on how was the performance in the examination.…”
Section: E Case Study On Active Learning Methodologies In Engineerinmentioning
confidence: 99%
“…This study investigates the process's capability to meet the customer specification requirement in machining Collection of data:-Students Group machined the components on the lathe, measured the dimensions of a part using a vernier calliper, and recorded the measurement of part manufactured for analysis. which is as shown in table 3 The group machined the parts on CNC used the advanced measuring instrument FARO Gauge to record the dimensions of part manufactured as shown in table 4 Statistical Analysis and Interpretation of Data:-Data collected for both conventional and CNC machines are analysed using MINI TAB Software [5] to analyse the variation present in subgroups and to know the values of Cp and Cpk. Knowing the values, students have concluded that the process is capable of producing parts according to customer specifications.…”
Section: Process Capability Analysis In Turning Operation (Conventionmentioning
confidence: 99%
“…Activity-Based Learning is a learning method that focuses on the role and participation of learners or Active Learning, which means a teaching style is encouraging learners to participate in Learning. The activity is based on student-teacher interaction (Patil, Budihal, Siddamal, & Mudenagudi, 2016). This kind of Learning was proved to improve the students' academic achievements and attitudes towards activities (Celik, 2018).…”
Section: Measurement 121 Treatment: Mobile English Learning Centermentioning
confidence: 99%